Integrasi Citra Satelit SPOT-7 dan GNSS-RTK dalam Penentuan Batas Administratif RT 5 Dusun Cisarua - Dwi Nanda Putra Hartoto; Muhammad Gunawan; Rahma Anisa; Romi Fadly (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2026)
The lack of clarity regarding administrative boundaries at the Neighborhood Unit (RT) level is a common problem in rural areas of Indonesia that has the potential to cause territorial disputes and hinder development planning based on spatial data. This community service activity aims to determine and document the administrative boundaries of RT 5, Cisarua Hamlet, Natar Village, Natar Subdistrict, South Lampung Regency, in a measurable manner using the integration of SPOT-7 satellite imagery and RTK geodetic GNSS observations. The methods applied include the creation of a working map based on SPOT-7 imagery, differential static GNSS surveys to determine GNSS-RTK control points tied to a CORS station, participatory boundary delineation with village leaders and officials, and the presentation of maps in accordance with BIG Head Regulation No. 3 of 2016 and BIG Regulation No. 15 of 2019. The results of the GNSS network processing showed control point position accuracy with a standard deviation of 1.1–2.7 mm. The administrative boundary of RT 5, Cisarua Hamlet, was defined by 19 cartometric points agreed upon by all parties without dispute. The output of the activity is a 1:1,000-scale RT 05 Cisarua Hamlet Boundary Map containing all mandatory cartographic elements along with a table of cartometric point coordinates. The integration of SPOT-7 and GNSS-RTK proved effective in producing a map of boundaries that is geometrically accurate and socially acceptable to the community, thus serving as a model for the application of geospatial technology in mapping community-scale administrative boundaries in rural areas of Indonesia.   Abstrak Ketidakjelasan batas administratif di tingkat Rukun Tetangga (RT) merupakan permasalahan umum di wilayah pedesaan Indonesia yang berpotensi menimbulkan sengketa wilayah dan menghambat perencanaan pembangunan berbasis data spasial. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk menentukan dan mendokumentasikan batas administratif RT 5 Dusun Cisarua, Desa Natar, Kecamatan Natar, Kabupaten Lampung Selatan secara terukur menggunakan integrasi citra satelit SPOT-7 dan pengamatan GNSS geodetik RTK. Metode yang diterapkan mencakup pembuatan peta kerja berbasis citra SPOT-7, survei GNSS statik diferensial untuk penentuan titik kontrol GNSS-RTK yang diikatkan pada stasiun CORS, delineasi batas secara partisipatif bersama tokoh dan perangkat dusun, serta penyajian peta mengacu pada Peraturan Kepala BIG Nomor 3 Tahun 2016 dan Peraturan BIG Nomor 15 Tahun 2019. Hasil pengolahan jaringan GNSS menunjukkan akurasi posisi titik kontrol dengan standar deviasi 1,1–2,7 mm. Batas administratif RT 5 Dusun Cisarua ditetapkan oleh 19 titik kartometrik yang telah disepakati seluruh pihak tanpa perselisihan. Luaran kegiatan berupa Peta Citra Batas RT 05 Dusun Cisarua pada skala 1:1.000 yang memuat seluruh elemen kartografis wajib beserta tabel koordinat titik kartometrik. Integrasi SPOT-7 dan GNSS-RTK terbukti efektif dalam menghasilkan peta batas yang akurat secara geometri sekaligus dapat diterima secara sosial oleh masyarakat, sehingga dapat menjadi model penerapan teknologi geospasial untuk pemetaan batas administratif skala komunitas di wilayah pedesaan Indonesia.